Assessing Diabetes Related Distress in Type 2 Diabetes Mellitus: A Prospective Interventional Study - Jacob, Rosmin; Sharma, Rajesh Kumar; Panayappan, L (Journal of Neonatal Surgery, 2025)
Background: Diabetes mellitus (DM) is a chronic metabolic disorder that often leads to diabetes-related distress (DRD), adversely affecting self-care, glycemic control, and increasing the risk of complications. Objective:To assess the prevalence and predictors of diabetes-related distress among type 2 diabetes mellitus patients and to evaluate its association with clinical parameters, complications, and sociodemographic factors. Methods: A prospective interventional study was conducted among 469 patients with type 2 diabetes patients. Inclusion criteria were adults aged ≥18 years with a diagnosis of type 2 diabetes for ≥6 months, while exclusion criteria included Type 1 diabetes and incomplete medical records. Participants provided informed consent, and ethical approval was obtained. Demographic, clinical, and psychosocial data were collected via patient interviews, with diabetes-related distress assessed using the DDS and PAID questionnaires. Statistical analyses included descriptive statistics, Spearman’s correlation, and logistic regression to identify predictors of distress, with p<0.05 considered significant. Results: The study revealed that 43.07% of patients experienced high emotional distress (PAID score >40), with emotional burden (38.17%) and regimen-related distress (26.43%) being the most common DDS subscales affected. Neuropathy (14.12%), retinopathy (11.88%), and slow wound healing (14.68%) were prevalent complications. Emotional distress was significantly associated with LDL (????=0.140, p=0.002), GRBS (????=0.143, p=0.002), BMI (????=0.128, p=0.006), and neuropathy (????=0.150, p<0.001). Logistic regression identified age >60 years, male gender, unmarried status, sedentary lifestyle, and comorbidities (neuropathy, retinopathy, nephropathy) as significant predictors of high diabetes distress and PAID scores. Conclusion: The emotional and psychological burden of managing diabetes, known as diabetes distress, plays a significant role in patients' overall well-being and disease management.